(untitled) (Medico Legal Update, 2021)
A cross-sectional school-based study was performed with the objectives to determine the prevalence of head lice infestation among primary schools in Baghdad suburbs (Abu Ghraib, Al-Yousifiya, Al-Radwaniyah, Al-Al-Taji, and Al-Hussainiya). The study included examination of 920 male and female students in several elementary schools’ class first to sixth (age 6-15 year). These schools include urban, rural, and economically and culturally diverse regions for the period from February to June 2018. The results of the current study showed that the total injury rate was 9%, and the Radwaniyah region recorded the highest infection rate of 13.2 and the Al-Al-Taji rejoin region recorded the lowest (6.1%). The female infection rate was greater than that of males and reached 12.3 and 5.6 respectively. The results indicated a significant relationship between the spread of head lice and the educational status of parents, sharing of the head comb, and infection with dandruff.